Ethics and Drug Resistance: Collective Responsibility for Global Public Health - Jamrozik, Euzebiusz; Selgelid, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This Open Access volume provides in-depth analysis of the wide range of ethical issues associated with drug-resistant infectious diseases. Antimicrobial resistance (AMR) is widely recognized to be one of the greatest threats to global public health in coming decades; and it has thus become a major topic of discussion among leading bioethicists and scholars from related disciplines including economics, epidemiology, law, and political theory. Topics covered in this volume include responsible use of antimicrobials; control of multi-resistant hospital-acquired infections; privacy and data collection; antibiotic use in childhood and at the end of life; agricultural and veterinary sources of resistance; resistant HIV, tuberculosis, and malaria; mandatory treatment; and trade-offs between current and future generations. As the first book focused on ethical issues associated with drug resistance, it makes a timely contribution to debates regarding practice and policy that are of crucial importance to global public health in the 21st century.
Introduction -- Part 1 Theoretical and conceptual approaches to ethics in antimicrobial resistance -- Chapter 1 The practical ethics of antimicrobial resistance as a collective action problem (Julian Savulescu) -- Chapter 2 Collective responsibility for antimicrobial resistance (Angus Dawson) -- Chapter 3 Moral aspects of antimicrobial stewardship (Marcel Verweij) -- Chapter 4 Ethical frameworks for rational antibiotic use (Annette Rid, Jasper Littmann, Alena Buyx) -- Chapter 5 The virtuous physician as antimicrobial prescriber (Justin Oakley) -- Chapter 6 Solidarity and compliance with antimicrobial policy (Søren Holm, Thomas Ploug) -- Chapter 7 Resistance, inequality, and epidemiological transition (Lynette Reid) -- Chapter 8 The price of precaution (Joakim Larsson, Christian Munthe) -- Part 2 Ethics and antimicrobial resistance in context -- Chapter 9 Hospital acquired infection (Lyn Gilbert & Ian Kerridge) -- Chapter 10 Antibiotic use in childhood (Michael Millar) -- Chapter 11 Ethics, animals, public goods (Jonny Anomaly) -- Chapter 12 Malaria (PY Cheah& Mike Parker) -- Chapter 13 Resistant HIV (Bridget Haire) -- Chapter 14 Access & availability of new TB drugs (Diego Silva, Adrian Viens, Jasper Littmann) -- Chapter 15 TB Resistance and Human rights (Leslie London) -- Chapter 16 TB Resistance in developing countries (Richard Coker, Marco Liverani, Mishal Khan) -- Chapter 17 Animal Epidemiology (Lisa Boden & Dominic Mellor) -- Part 3 Ethical, legal and economic aspects of antimicrobial resistance -- Chapter 18 Privacy and data collection(Leslie Francis) -- Chapter 19 Mandatory treatment interventions (Carl Coleman) -- Chapter 20 Ethics and AMR Regulation (Belinda Bennett) -- Chapter 21 Ethics of Drug Development (Nick King) -- Chapter 22 Economics of resistance (Coast/Smith) -- Conclusion.
Keywords: Bioethics; Medical microbiology; Diseases; Bioethics; Medical Microbiology; Diseases